2017
DOI: 10.2739/kurumemedj.ms644001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorella Ingestion on Oxidative Stress and Fatigue Symptoms in Healthy Men

Abstract: Our results suggest that chlorella ingestion has the potential to relieve oxidative stress and enhance tolerance for fatigue under resting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies have also confirmed that exhaustive exercise will cause damage to the liver tissue of the body to a certain extent. After excessive exercise, the active oxygen and other substances and oxidative stress levels in the body are significantly increased [ 12 , 13 ]. Therefore, improving the body's ability to resist oxidative stress is of great significance for preventing cardiovascular system damage after EIF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also confirmed that exhaustive exercise will cause damage to the liver tissue of the body to a certain extent. After excessive exercise, the active oxygen and other substances and oxidative stress levels in the body are significantly increased [ 12 , 13 ]. Therefore, improving the body's ability to resist oxidative stress is of great significance for preventing cardiovascular system damage after EIF.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorella, more specifcally Parachlorella beijerinckii, has been used as a dietary supplement in Japan for about ffty years and no side efects have been observed. Its continuous ingestion for 6−16 months in animal experiments or for 1−5 months in clinical trials was also not associated with adverse efects [23,24,36,[44][45][46][47]. Because the accumulation of AGEs in the skin occurs over many years, long-term ingestion is desirable for prevention.…”
Section: Discussionmentioning
confidence: 99%